Pengaruh Latihan Quickness terhadap Peningkatan Kecepatan Tendangan Atlet Kategori Tanding Cabang Olahraga Pencak Silat - Anugrah, Nurul; Permadi, Asep Angga; Sonjaya, Azhar Ramadhana (Ilmu Olahraga, 2022)
This study aims to determine the effect of quickness training on increasing kick speed of athletes in the competition category of pencak silat. The method in this study is a quasi-experimental design (quasi-experimental design) with a pretest-posttest control group design. The population in this study were athletes assisted by IPSI Garut Regency in the competition category, amounting to 20 adults in the age group. The sampling technique is using a saturated sampling technique, namely by taking the overall sample from the population. Technical analysis of the data in this study using the t test (paired sample t-test). The results of data analysis showed that there was a significant effect on increasing the speed of athletes in the competition category for the sport of pencak silat. The results of the t-test for the test of the number of kicks obtained a t-count value of 4.811 while the t-table is 0.001. Means greater than ttable, then (H0 is rejected), in addition to the results obtained from the output of Pair 1 pretest and posttest the experimental group obtained a Sig value. (2-tailed) 0.001 < 0.05 and for the time speed t-test the t-test value is 6.029 while the t-table is 0.000. Means greater than ttable, then (H0 is rejected), in addition to the results obtained from the output of Pair 1 pretest and posttest the experimental group obtained a Sig value. (2-tailed) 0.00 < 0.05. So it can be concluded from the results of the two tests that quickness training has a significant effect on the kick speed of athletes in the competition category of pencak silat.